Advancing Audiovisual Translation Education: Evaluating and Enhancing the Capabilities of English Undergraduates at the University of Mataram - Wardana, Lalu Ali; Baharuddin, Baharuddin; Farmasari, Santi (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2024)
This study aims to evaluate and develop the audiovisual translation (AVT) skills of English education undergraduate students at the University of Mataram. As the dissemination of information increasingly occurs through dynamic online media, mastering AVT techniques has become essential for future language professionals. The study will examine the quality of subtitle translations produced by students, as well as their ability to translate audio content into video captions - a new skill beyond traditional dubbing. By assessing current capabilities, the study seeks to reorient translation course curricula to better balance theoretical knowledge and practical application. Given the rapid technological advances in AVT, this study is critical in ensuring university programs adapt to emerging industry needs. The findings are expected to contribute to improving the quality of AVT education and enhancing the preparedness of English undergraduates to work as professional audiovisual translators. Ultimately, the study aims to empower the next generation of translators with the necessary skills to effectively convey information across multimedia platforms.